Dinâmica do fósforo em ecossistema de pastagem natural submetido à aplicação de fontes de fosfato - Oliveira, Leandro Bittencourt de (2012)
The knowledge of P dynamics in grassland ecosystems may be important to prescription of changes caused by the addition of different sources of phosphate fertilizers in the P forms of soil, dry matter production and botanical composition of natural grasslands. The objective of this work was to evaluate the dynamics of P (a) the availability and forms of P; (b) total dry matter and contributions in dry matter and (c) dilution curves of P content from tissue of main species of natural grasslands after the application of different phosphate sources in three soil types under natural grasslands with or without historical of P applications. Treatments were P applications as Gafsa rock phosphate, simple superphosphate, triple superphosphate and control, arranged in randomized blocks with three replicates. In two experiments located in the city of Candiota - RS (Ultisol and Entisol), 100 kg ha-1 P2O5 were applied in September 2010. In the experiment of Santa Maria - RS (Alfisol), 180, 90, 100 e 100 kg ha-1 P2O5 were applied in 1997, 1998, 2002 and 2010, respectively, which represent 470 kg ha-1 P2O5. The soil samples (0-10 cm) and herbage mass were evaluated in the spring and summer after applied the last treatment in each experiment. The Gafsa rock phosphate showed a potential to increase P availability in soils with low calcium content in natural grasslands, but increases were higher when superphosphate was used. The application of phosphate fertilizers in soils under grasslands increases the importance of inorganic fractions of labile P to the available P to plants, making them less dependent on the mineralization of organic fractions. The P fertilization response was higher where annual species occurrence prevailed. In pastures with historical of fertilization, contribution of main species to the total dry mass of pasture had changed. In Candiota city, species did not grow by a severe drought. In Santa Maria, species as Paspalum notatum, Aristida laevis and other plants aggregated as Other Species had increased biomass and P tissue content was diluted over the periods. The specie Eustachys ulignosa had responded in biomass to soluble phosphate additions. The evaluated phosphates sources did not alter the N content in the tissue of grassland species.